Dynamic modeling for diameter distribution on Pinus mixed stands in Durango, Mexico - Quiñonez Barraza, Gerónimo; De los Santos Posadas, Héctor Manuel; Cruz Cobos, Francisco; Velázquez Martínez, Alejandro; Ángeles Pérez, Gregorio; Ramírez Valverde, Gustavo (Instituto de Ecología, A.C., 2016)
The characterization of the diameter distributions provides information on the structure of a stand and support in the planning of silvicultural treatments in forests with management. We estimated the parameters of location, scale and shape of the Weibull function to characterize the diameter distribution of species mixture of Pinus. We used 59 plots for model fitting (900 m2) and 100 temporary forest inventory plots for validation (1000 m2). The method of moments was better to estimate the parameters of the Weibull function as statistics used to measure the goodness of fit (lower mean absolute error, lower mean square error and fewer rejected plots with Kolmorogov-Smirnov test) compared with maximum likelihood and percentile methods. The prediction models of the parameters with stand variables represent a flexible and simple way to characterize and project the theoretical distribution of diameter classes easily and accurately. The kurtosis of the Weibull distribution has less peakedness with the projection of the number of trees in diameter classes, the shape of the curve tends to normalize and a slight positive skewness, while basal area in the form is more theoretical platykurtic distribution. The projection of the Weibull distribution can be used to determine forest management regimes or to regularize diameter structures in uneven-aged stands.